Crustal Structure Across the Northern Region of the Islas Marías Archipelago - Madrigal, Luis Alfredo; Núñez, Diana; Escalona-Alcázar, Felipe de Jesús; Núñez-Cornú, Francisco Javier (Frontiers in Earth Science, 2021)
The tectonic interaction between the Rivera and North American plates north of the Bahía de Banderas is poorly understood. The nature of the crust and where the subduction ends in the western part of the Islas Marias Archipelago are still controversial. Based on new geophysical data provided by the TsuJal project, we present the shallow and deep crustal structure of the Rivera - North American plate contact zone along two seismic transects, TS09b and RTSIM01b, and the bathymetry obtained across the northern region of María Madre Island. Detailed bathymetric analysis allowed mapping of a series of lineaments along the study region, with two main preferred tendencies (020°-050° and 290°-320°) associated with the evolution of the Pacific-Rivera Rise and the transform faults of the Gulf of California, respectively. The shallow structure is characterized by five sedimentary basins without deformation, whose horizons are sub-parallel suggesting that the sediment deposition occurred after the extension process ended. The deep structure corresponds to a transition between oceanic crust (Rivera plate), with an average thickness of ~10 km to the Islas Marías Escarpment, and a thinned continental crust, whose thickness increases towards the continent until it reaches 28 km, with a dip angle of 7°-10°. The absence of an accretionary prism suggests that the subduction process of the Rivera plate beneath the North American plate to the north of Islas Marías has ceased. In this study, we determined that the morphological expression of the northern limit of the Rivera plate corresponds to the Islas Marías Escarpment.